PENGARUH STRATEGI PEMBELAJARAN DAN MINAT BERWIRAUSAHA TERHADAP HASIL BELAJAR MENJAHIT DENGAN MESIN SISWA SMK NEGERI 8 MEDAN - Nurhayati Tanjung (Universitas Negeri Medan, 2015)
ABSTRACT This research aims to know the influence of learning process and the interest to enterpreneurship to the result of learning sewing with machine in SMK Negeri 8 Medan students.. This research was conducted at SMK NEGERI 8 MEDAN. The population of the research was the whole grade X students of Tata Busana. The research method of this study used Quasi experimental research design with a factorial 2 x 2. Learning strategies that were used in this study are contextual learning strategies and expository learning strategy. The interest of entrepreneurship was categorized as over high and low. The research results shows that contextual learning strategies are better taught to students who are interested in entrepreneurship and strategy of high learning well used expository to students who are interested in entrepreneurship are low, and there is interaction between the learning strategies and interests of entrepreneurship with the results of learning to sew with a machine. Kata Kunci : Strategi Pembelajaran, minat berwirausaha, hasil belajar.